The effects of sports vision training on binocular vision function in female university athletes - Zwierko, T.; Puchalska-Niedbal, L.; Krzepota, J.; Markiewicz, M.; Wozniak, J.; Lubinski, W. (Journal of Human Kinetics, 2015)
Binocular vison is the most important visual cue for spatial orientation in many sports. In this study, we investigated how binocular vision was influenced by an eye training program that may be used to improve individual`s oculomotor function. The experiment involved twenty-four female student athletes from team ball sports (soccer, basketball, handball). After an initial testing session, 12 participants were randomly allocated to the experimental group. Optometric investigation which included synoptophore testing and a test of dissociated horizontal phoria based on the Maddox method was performed three times: before the experiment, after eight weeks of eye training (3 times a week for 20 minutes), and four weeks after the experiment was terminated. Eye exercise methodology was based on orthoptic, sport and psychological aspects of performance. The phoria screening examination showed that exophoria was the most frequent disorder of binocular vision. Low fusional vergence range was also observed. Following the training period, 3 of the 6 oculomotor variables improved. The greatest effect was observed in near dissociated phoria (?²=14.56, p=0.001 for the right eye; ?²=14.757, p=0.001 for the left eye) and fusional convergence (?²=8.522, p=0.014). The results of the retention test conducted four weeks after the experiment confirmed the effectiveness of the vision training program. The results of the study suggest that binocular functions are trainable and can be improved by means of appropriate visual training